Seasonal variation in semen quality: effect of temperature: a study in North India - Balhara, Kirti; Singh, Sarika; Sharma, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Variable temperature in different seasons may affect the quality of semen. Most of the studies are from west barring a single large Chinese study with variable results; however, no such study focusing on temperature alone has been published from Indian subcontinent. Present study was undertaken to observe any seasonal variation affecting the semen quality at different times of year. Methods: The study was conducted retrospectively over one year period (2014-2015) at a tertiary care hospital in North India. 815 semen samples referred from infertility clinic were analysed for Sperm concentration, functional sperm concentration, motile sperm concentration and sperm motility index by an automated semen analyser system (SQAIIC-P, Medical Electronic Systems, Los Angeles, CA, USA); and morphological assessment by Papanicolaou stained smears. Statistical analysis was done using SPSS 24 software (SPSS Inc, Chicago, IL, USA). The ANOVA test was used to assess differences in semen parameters, p<0.05 was considered as statistically significant. Results: Depending on the average highest temperature (AHT) in different seasons, samples were categorized in four groups: winter AHT <10°C, spring AHT <20°C, autumn/rainy season AHT 20-30°C and summer AHT >30°C.There was significant variation on different parameters e.g. sperm count, motility, FSC, MSC, SMI, abnormal sperms and morphological defects when compared in different groups using ANOVA test (p<0.05). Conclusions: Present study observed that AHT of 20-30°C (autumn) has a favourable effect on semen quality; however, larger and continuous data in the form of longitudinal study is needed for better correlation.